21st CENTURY SKILLS PROFILE OF STUDENTS IN THE RESEARCH METHODOLOGY COURSE OF THE 2018 BIOLOGY EDUCATION STUDY PROGRAM, MEDAN STATE UNIVERSITY - Dina Fitriyani Saragih; Halim Simatupang (Jurnal Pelita Pendidikan, 2023)
This research study aims to determine the 21st Century Skills Profile of students in the research methodology course for the 2018 Biology Education Study Program, Faculty of Mathematics and Natural Sciences, State University of Medan. This research was conducted in December-March 2021 in the Biology Education Study Program, Faculty of Mathematics and Natural Sciences, UNIMED. This study used a mixed descriptive method with a sequential explanatory strategy and a sampling technique, namely random sampling of 109 students. The data analysis technique used in this research is descriptive statistical analysis techniques for quantitative data and interactive analysis for qualitative data. Data were collected using a questionnaire and interview instruments. The results showed the 21st Century Skills Profile of students in the research methodology course for the 2018 Biology Education Study Program, Faculty of Mathematics and Natural Sciences, State University of Medan was included in the good criteria with a percentage of 77,81%.